2016
DOI: 10.1038/srep39353
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of Complementary Ternary Graphene Field-Effect Transistors

Abstract: Strong demand for power reduction in state-of-the-art semiconductor devices calls for novel devices and architectures. Since ternary logic architecture can perform the same function as binary logic architecture with a much lower device density and higher information density, a switch device suitable for the ternary logic has been pursued for several decades. However, a single device that satisfies all the requirements for ternary logic architecture has not been demonstrated. We demonstrated a ternary graphene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…For instance, negative-differential conductance (NDC) devices and negative-differential transconductance (NDT) transistors, which comprise diverse kinds of materials ( e.g. , biomolecule complexes, organic materials, carbon nanotubes, graphene, , van der Waals heterostructures, oxide composites, , silicon (Si) nanostructures, etc . ), are typical examples that can realize the MVL computing system beyond modern binary digital technology.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, negative-differential conductance (NDC) devices and negative-differential transconductance (NDT) transistors, which comprise diverse kinds of materials ( e.g. , biomolecule complexes, organic materials, carbon nanotubes, graphene, , van der Waals heterostructures, oxide composites, , silicon (Si) nanostructures, etc . ), are typical examples that can realize the MVL computing system beyond modern binary digital technology.…”
Section: Introductionmentioning
confidence: 99%
“…In the TCMOS, the off-current (I OFF ) levels of NMOS (n-type MOS) and PMOS (p-type MOS), which are generated by band-to-band tunneling (BTBT), should be matched to form the third V out state during inverter operations. In contrast to conventional ternary devices that utilize multithreshold voltage (Multi-V t ) transistors [6][7][8][9][10][11][12], the TCMOS can perform ternary operations using a pair of NMOS/PMOS with a single voltage (V t ); the fabrication process is also comparable to the conventional CMOS process, because it can be fabricated only by introducing one additional doping process. However, the TCMOS has the disadvantage of slow switching speed caused by low on-state current (I ON ).…”
Section: Introductionmentioning
confidence: 99%
“…he demand for more functionality at lower power consumption has been driving the limit of complementary metal-oxide-semiconductor (CMOS) technology [1]. Multi-valued logic (MVL) has been pursued for several decades because it can provide significant advantages to reduce the complexity of interconnects and the arithmetic operations [2]- [11]. Various types of single or composite devices exhibiting multiple states have been investigated for this purpose.…”
Section: Introductionmentioning
confidence: 99%
“…Shim et al demonstrated a ternary inverter using the graphene/WSe2 heterojunction, which showed light-induced negative differential transconductance (NDR) characteristics [10]. Kim et al demonstrated a complementary ternary logic device using graphene FET with npn and pnp channel profiles [11]. These devices showed the feasibility of the ternary logic device function with a low thermal budget integration process; however, their performances are not competitive to silicon devices yet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation